Extracellular protease from Bacillus subtilis B315 with antagonistic activity against bacterial wilt pathogen (Ralstonia solanacearum) of chili : - - Nur Prihatiningsih; ARI ASNANI; HERU ADI DJATMIKO (Society for Indonesian Biodiversity, 2021)
Abstract. Prihatiningsih N, Asnani A, Djatmiko HA. 2021. Extracellular protease from Bacillus subtilis B315 with antagonistic activity against bacterial wilt pathogen (Ralstonia solanacearum) of chili.  Biodiversitas 22: 1291-1295. Antagonistic bacteria isolated from a healthy potato are potential biocontrol agents against a number of bacterial pathogens. The capability of antagonistic bacteria to produce extracellular protease could be considered as an indicator of their antagonistic capacity. The objective of this research was to study the optimum activity of protease produced by Bacillus subtilis B315 to control Ralstonia solanacearum causing wilt of chili. In this research were optimum incubation time, pH and crude extract protease concentration of B. subtilis B315 examined for maximum production of extracellular protease. The results showed that B. subtilis B315 was capable of producing protease at optimum incubation time of 30 min, pH 9, and crude extract protease concentration 0.50% with an activity of 1.3185 U/mL. Protease-producing capability of B. subtilis B315 was shown by the formation of a clear zone around the colony of B. subtilis B315 grown on skim-milk agar medium. B. subtilis B315 was capable of inhibiting the growth of R. solanacearum in vitro as indicated by 32 mm clear zone. Furthermore, in chili application of B subtilis showed that this bacteria was capable of controlling chili bacterial wilt caused by R. solanacearum with effectiveness of 60.89%. The prospective of B. subtilis B315 could be formulated as biopesticide.